Opening Doors to Independence: Why Your Child’s IEP Should Include Recreational Therapy for Leisure Skills - Archambault, MaryJo; Terpstra, Judy (PALAESTRA, 2026)
Leisure, as the pursuit of activities we choose to engage in during our free time, holds immense potential for enriching our lives. However, individuals with disabilities often face barriers that hinder their ability to participate fully in leisure activities. The delivery of leisure education to students in Special Education is of paramount importance in promoting independence and quality of life. This exploratory study investigates the delivery of leisure education to students in transition programs, aiming to understand current practices. In addition, this paper makes an argument for the inclusion of recreational therapists in the transition setting and encourages guardians to request recreational therapy as a related service on their child’s Individual Education Plan (IEP).
Keywords: dept.rec; dept.sed

Teacher and parent perspectives on extracurricular activities for students with intellectual and developmental disabilities - Cain, Irina; Bruno, Lauren; Agran, M.; Wojcik, Andrew; Achola, Edwin; Thoma, Colleen; Nixon, Cynthia; Tamura, Ronald (Inclusion, 2025)
Keywords: Extracurricular activity; Intellectual disability; Qualitative research; Semi-structured interview; dept.sed

Introduction to the special section on drivers with ASD - Volkmar, Fred (Journal of Autism and Developmental Disorders, 2025)
Keywords: Autism; Clinical psychology; Computer science; Developmental psychology; Engineering; Engineering physics; Medicine; Psychology; Public health; Section (typography); Special section; dept.sed

Considering emerging, complementary, and alternative treatments - Øien, Roald; Nordahl‐Hansen, Anders; Skarbek, Sacha; Tolkin, Samuel; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Computer science; dept.sed

Evidence-based practices in autism: where we started to where we are now - Reichow, Brian; Doehring, Peter; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Developmental psychology; Psychology; dept.sed

Evidence-based practices and treatments in autism spectrum disorder: concluding thoughts - Volkmar, Fred; Doehring, Peter; Reichow, Brian (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Autism spectrum disorder; Cognitive psychology; Developmental psychology; Physics; Psychology; Spectrum (functional analysis); dept.sed

AI in Special Education: Bridging Gaps, Easing Workloads, and Inspiring Inclusion - DiBattista, Eileen; Erazmus, Kelly; Tucker, Lauren (Teaching Exceptional Children, 2025)
Keywords: Bridging (networking); Inclusion (mineral); Learning disability; Special education; Teaching method; dept.sed

From Theory to Practice: A Tiered Support Model for Increasing Preservice Teachers’ Use of Behavior Specific Praise - Hynes, Kristy; Gershwin, Tracy (Journal of Educational and Psychological Consultation, 2025)
Keywords: Praise; Qualitative research; Work (physics); dept.sed

Assistive Technology Multi-Tiered System of Supports (AT-MTSS): Improving AT Delivery - McMahon, Don; Tucker, Lauren (Journal of Special Education Technology, 2025)
Keywords: Assistive technology; CLARITY; Inclusion (mineral); Psychological intervention; Special education; Special needs; Universal Design for Learning; Variety (cybernetics); accessibility; assistive technology; dept.sed; multi-tiered systems of supports; special education teacher preparation; universal design for learning

Centering Critical Engagement, Multimodal Learning, and Compassion through Language and Literacy - Mulcahy, Cara; Shaw, Louise (The Intersections of Critical Pedagogy, Critical Literacy, and Social Justice: Toward Empowerment, Equity, and Education for Liberation, 2024)
Keywords: dept.sed

Self-Monitoring to Reduce Student Distraction in Higher Education - Brahm, Meghan; Hynes, Kristy (College Teaching, 2025)
Keywords: Applied behavior analysis; Cognitive psychology; Distraction; Higher education; Mathematics education; Pedagogy; Political science; Psychology; Student engagement; classroom distraction; dept.sed; higher education; self-monitoring; student engagement

Building TRUST: Empowering Teachers to Support Students With Emotional and Behavioral Disorders - Mitchell, Carolyn; Gershwin, Tracy; Robinson, Jason; Hynes, Kristy (Intervention in School and Clinic, 2025)
Keywords: Applied psychology; Developmental psychology; Emotional and behavioral disorders; Learning disability; Mathematics education; Pedagogy; Psychology; Reading (process); Special education; dept.sed; peer-reviewed

Autism spectrum disorder in adolescents and adults: an introduction - Volkmar, Fred R.; Reichow, Brian; McPartland, James C. (Adolescents and Adults with Autism Spectrum Disorders, 2024)
Leo Kanner’s classic description of autism appeared eight decades ago. Although the pace of research has increased dramatically, research specifically focused on adolescents and adults remains limited in many respects. Numerous outcome studies have been conducted and suggest potential for markedly improved outcome with intervention. Unfortunately, studies on adults after early adulthood are sparse and, for old age, almost nonexistent, reflecting a lack of support for research in this population. This is in stark contrast to other developmental disorders in which considerable information on adult life is often available. This book summarizes work across areas, focusing on what is known and not yet known, highlighting important areas for future research. While overall outcome has improved, a small group of individuals remain in need of high levels of adult care. For all individuals, the field requires new approaches to both research and clinical service.
Keywords: Adolescents; Adults; Autism; Outcome; Supports; dept.sed

Brief Report: Bullying and Anxiety in High-Functioning Adolescents with ASD - van Schalkwyk, Gerrit; Smith, Isaac C.; Silverman, Wendy K.; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Youth with ASD are more likely to experience bullying than their typically developing peers. This risk has not been studied in youth with ASD transitioning to college. We examined the occurrence of bullying in 35 high functioning youth with ASD who were preparing to attend college. We also examined youth anxiety and ASD symptoms. Fifty-one percent of the sample reported being recent victims of bullying; 31% of parents reported their child was a victim of bullying. Parent report of bullying correlated significantly with ratings of youth social anxiety symptoms. These findings suggest that bullying is an issue of concern for higher functioning, older adolescents with ASD, and that their own reports may be particularly important in identifying its occurrence.
Keywords: Anxiety; Autism spectrum disorder; Bullying; Postsecondary education; dept.sed

Preface: Special Issue—College Experiences for Students with Autism Spectrum Disorder - Jackson, Scott L. J.; Hart, Logan; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

Educational Professionals’ Decision Making for Professional Growth using a Case of Twitter Adoption - Tucker, Lauren (TechTrends, 2019)
This paper is a report of an examination of educational professionals’ perspectives on their decision processes to use a Twitter personal learning network (PLN). When investigating each of the participants’ decision-making processes to accept or reject the use of a Twitter PLN, the externally supported individualized learning experience was integral to the educational professionals’ active decision to adopt the new tool. The five major findings revealed external stimulus and support is (1) vital to address pre-existing attitudes and beliefs, (2) to target the acquisition of technical and implementation knowledge, and (3) to encourage continued exposure, interaction, and exploration. The final two findings focus on the (4) interaction with a social learning community supports decision making and informal learning, and (5) personal experimentation and exploration of a Twitter PLN allows educational professionals to build their professional network, quickly access high quality information, and read educational material. Educational professionals’ informal learning activities were also revealed while using their PLN. Educational professionals reported sharing information and resources with colleagues as having the most significant impact on professional practice. In addition to interviews, the nature of the Twitter platform provided valuable evidence of informal learning activities. These activities reflected in the educational professionals’ tweets included: reading educational subject matter, reflection and collaboration. Also, a new category: Resource Collection was created to reflect the second most popular activity on educational professionals’ Twitter PLN.
Keywords: Decision Making; Digital Education and Educational Technology; Informal Learning; Personal Learning Network (PLN); Professional Growth; Social Media; Twitter; dept.sed

Relationships Matter: The Art of Creating Meaningful Interactions With Students - Hynes, Kristy; Gershwin, Tracy; Robinson, Jason; Mitchell, Chrissa (Beyond Behavior, 2025)
Keywords: Foundation (evidence); Mathematics education; Pedagogy; Psychological intervention; Psychology; dept.sed; peer-reviewed

Impacts of an assistive technology graduate program: a case study - Tucker, Lauren (Assistive Technology Outcomes and Benefits (ATOB), 2024)
Alumni from an Assistive Technology (AT) graduate program were invited to complete a survey and participate in focus groups to share how they are using the knowledge gained from their graduate degree and its impact on their professional careers. The sample of 27 alumni spanned seven years and a variety of professional backgrounds. This qualitative single-case study revealed impacts on careers, professional skill development, and technology skills after graduation. Participants also connected this later skill development to their concrete learning experiences within the graduate program.
Keywords: assistive technology; dept.sed; graduate program; peer-reviewed; perspectives; special education

Letter to the editor: Supporting drivers with autism and police officer interactions-Connecticut’s blue envelope program - Gleeson, M.B.; Grindle, H.; Gleeson, M.M. (Journal of Autism and Developmental Disorders, 2024)
The rising prevalence of autism spectrum disorder (ASD) has led to increased efforts to support individuals with ASD across numerous aspects of life, including driving. While obtaining a driver’s license substantially impacts quality of life and independence, it also creates distinct challenges for those with ASD. Challenges surrounding social communication, executive functioning, and sensory sensitivities are particularly evident when considering interactions between drivers with ASD and law enforcement personnel. Connecticut’s Blue Envelope Program aims to improve interactions between drivers with and ASD law enforcement by providing instructions for officers and drivers to follow during routine traffic stops on a physical, blue colored, envelope. The instructional guidelines aim to assist officers in understanding and appropriately responding to common ASD-related behaviors which may be otherwise misinterpreted and includes accommodations officers could consider during a stop. Additionally, the envelope outlines clear steps for drivers with ASD to follow through the stop as to support predictability and expectations. The widespread acceptance, efficacy and popularity of the Blue Envelope program underscores the importance of increasing awareness and understanding of ASD among law enforcement and the need for more supports to aid in these increasing interactions. Discussion is offered on a broader implementation of this program to support individuals with ASD and officers, while improving the outcomes of interactions. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.
Keywords: Autism; Blue envelope; Driving; Law enforcement; Police officers; dept.sed

Adapted text benefits for teachers and students: A retroactive case study - Tucker, Lauren (Journal of Learning and Teaching in Digital Age, 2021)
This case study retrospectively reflects on a self-contained teacher’s decision to pair publisher-created adapted text with audio support as part of a multicomponent reading intervention. She evolved from creating her own adapted text to implementing publisher-created adapted text throughout a school year. The study analyzed students’ reading comprehension test scores throughout the year to examine the influence of publisher-created adapted text embedded within a multi-component reading intervention. The Related-Samples Wilcoxon Signed Rank Test revealed significance (p=.043) between students’ fall and spring Reading Inventory scores, with a moderate effect size (r=.562). The teacher made the instructional decision to implement publisher-created adapted text which eliminated time consuming self-adaptation of materials (Browder et al., 2007) and her students continued to make progress with this shift of materials with some demonstrating significant progress by the end of the school year.
Number: 1
Keywords: dept.sed

Universally Designing in Universal Chaos. - Tucker, Lauren (Remote Teaching and Learning: Reflections and Practical Advice, 2021)
Looking back on a year of tumultuous teaching and learning amid restrictions set in place after the COVID-19 pandemic began in early 2020, Remote Teaching and Learning: Reflections and Practical Advice focuses not only on the trials and tribulations higher ed faculty have endured but also the insights learned, silver linings revealed, and successes achieved through emergency remote teaching. Hear from 20 educators whose contributions include: reflections on pandemic teaching; strategies and practical advice; and resources for students.Whether you’re returning to a face-to-face classroom, continuing to teach online, or exploring hybrid or HyFlex teaching, you’ll find wisdom, advice, and observations from educators with a shared commitment to student learning. Includes student handouts to use in your classroom!
Keywords: dept.sed

Whither Asperger’s post DSM-5? An opinion piece - Volkmar, F.R.; Woodbury-Smith, M. (Review Journal of Autism and Developmental Disorders, 2024)
Although first described in 1944 (the year the description of infantile autism), Asperger’s syndrome attracted little attention until the publication by Lorna Wing in early 1980. Over time, different views of the definition of Asperger’s syndrome developed. By the time of the Third Edition of the American Psychiatric Association’s Diagnostic and Statistical Manual and the Tenth Edition of the World Health Organization’s International Classification of Disease, enough information had accumulated to include the condition within the broader autism category. Asperger’s syndrome remained a focus of research interest and debate until its exclusion in the DSM-5 in 2013. We argue that the decision to remove Asperger’s syndrome 10 years ago as a distinct condition was premature. A discussion of the tensions around defining Asperger’s and concerns now arising due to the lack of this diagnostic category for new cases is provided. © 2024, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Asperger’s disorder; Autism spectrum disorder; Autistic disorder; Classification; DSM-5; dept.sed; peer-reviewed

Culturally Responsive Special Education - Gerzel-Short, Lydia; Jerae, Kelly; Hovey, Katrina A.; Hsiao, Yun‐Ju; Wei, Yan (Advances in educational marketing, administration, and leadership book series, 2023)
Keywords: dept.sed

Preparing culturally responsive teachers: a systematic review - Miller, Rhonda D.; Gerzel-Short, Lydia; Kelly, Jerae H.; Uphold, Nicole; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan (Multicultural Learning and Teaching, 2023)
As the world continues to ponder issues of equity and diversity, U.S. public schools face an expanding demographic divide between teachers and students. While diverse groups of public school students show an increase in population, the teaching workforce in the U.S. remains overwhelmingly White. The purpose of this systematic review is to examine how preservice teachers (PST) are being prepared to be culturally responsive. A total of 26 studies published between 2006 and 2020 were reviewed. The results indicate that PSTs’ learning experiences are varied and tend to be stand-alone approaches focused on changing the attitudes and beliefs of PSTs. Findings also bring to light the vagueness of terminology used in the research to define cultural groups of students, the conspicuous absence of studies related to LGBTQ+ populations, and the lack of study replications. Implications for future research are discussed.
Keywords: culturally responsive; dept.sed; diversity; peer-reviewed; pre-service teacher; teacher education; teacher preparation

Developing simulation materials to support teacher anti-racist and anti-ableist practice during iep meetings: Supporting general educator collaborative practice - Perouse-Harvey, Ebony (Advocating and Empowering Diverse Families of Students With Disabilities Through Meaningful Engagement, 2023)
Research demonstrates discriminatory and inequitable practices related to students identified with (disabilities). Inequitable practices and discrimination reveal the necessity of collaboration and advocacy as an integral part of the pedagogy of professional development for members of the IEP team. Providing pre-service (or preparing) teachers simulated experiences of individualized education program (IEP) meetings can support PSTs understanding of how ableism and racism can manifest in schools, develop skills in collaborating with families, and begin to develop advocacy practices that support students that are marginalized at the intersection of their race and ability status. This chapter focuses on how to develop materials that leverage critical theoretical frameworks, provide learning experiences that mirror teacher practice in schools, and provide authentic representations of families of color to develop PSTs collaborative and advocacy practices. © 2023 by IGI Global. All rights reserved.
Keywords: dept.sed

Training and Identity in a Collaborative Program. - Major, Patricia (2003)
Keywords: dept.sed; faculty_collection; sabbatical_report

Assistive Technology in the Classroom: Enhancing the School Experiences of Students with Disabilities - Dell, Amy G.; Newton, Deborah A.; Petroff, Jerry G. (Pearson, 2015)
Keywords: Educational technology; United States; United States; Students with disabilities; dept.sed; faculty_collection

The Power of RTI and Reading Profiles: A Blueprint for Solving Reading Problems - Spear-Swerling, Louise (Paul H. Brookes Publishing Co., 2015)
"The reading problems addressed in the book move beyond those associated with disabilities such as dyslexia or high-functioning autism. The author addresses experientially based reading difficulties caused by inadequate instruction or limited exposure to academic language/literacy. Unlike other books on response to intervention (RTI), this book presents an argument for using RTI as a method of identification as well as intervention in combination with individual students' reading profiles. The case studies and practical examples cover a broad range of reading problems (not only learning disabilities) to help make research findings applicable to a multidisciplinary audience, especially practitioners"–
Keywords: Reading disability; Reading; Remedial teaching; Response to intervention (Learning disabled children); dept.sed; faculty_collection

Assistive Technology in the Classroom: Enhancing the School Experiences of Students with Disabilities - Dell, Amy G.; Newton, Deborah A.; Petroff, Jerry G. (Pearson, 2012)
Keywords: Educational technology; United States; United States; Students with disabilities; dept.sed; faculty_collection

Assistive Technology in the Classroom: Enhancing the School Experiences of Students with Disabilities - Dell, Amy G.; Newton, Deborah A.; Petroff, Jerry G. (Pearson Merrill Prentice Hall, 2008)
Keywords: Educational technology; United States; United States; Students with disabilities; dept.sed; faculty_collection

Increasing outcomes: principles of practice to increase writing outcomes for deaf/hard of hearing students with additional disabilities - Weir, Joan; Dostal, Hannah M. (Strategies for Promoting Independence and Literacy for Deaf Learners With Disabilities, 2023)
The ability to write clearly and effectively is an important communication skill that is necessary for school and employment, as it is often the best way to disseminate information and ideas. Both unrecorded sign and speech are ephemeral, but writing allows the author to share an experience or idea...
Keywords: dept.sed

Autism and intersectionality: Considerations for school-based practitioners - Sassu, Kari A.; Volkmar, Fred R. (Psychology in the Schools, 2022)
The purpose of this article is to explore the intersectionality of autism and sociocultural factors as well as discuss the complexities associated with appropriate assessment, diagnosis, and intervention. Based on a review of the literature, the authors present a brief history of the emergence of the term autism and highlight factors that have contributed to current concerns about failures to appropriately recognize autism within diverse populations. Referencing extant research as well as professional practice standards, this article examines aspects of autism and intersectionality, and explores some of the associated challenges related to assessment, diagnosis, and intervention. Further, the authors reflect on the critical importance of carefully considering all aspects of a child's identity when engaging in autism assessment and intervention within the school setting. School-based practitioners are provided with guidance for addressing the needs of diverse populations of students with autism.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pits.22757
Keywords: SES; autism; dept.csp; dept.sed; ethnicity; intersectionality; peer-reviewed; race

Education of students with visual impairments in Kenya: Trends and issues - Kiarie, M.W. (International Journal of Special Education, 2004)
Until the nineteen hundreds, people with disabilities did not receive formal educational services in Kenya. This paper discusses available educational services for individuals with visual impairments in terms of their forms, materials provided, and educational placements. Areas of most progress are discussed along with obstacles that stand in the way of efficient services for this population. This paper contributes to the rather scarce literature on educational services for students with disabilities in developing countries.
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Educational services for students with mental retardation in Kenya - Klarie, M.W. (International Journal of Special Education, 2006)
Research pertaining to issues on educational services for individuals with disabilities in developing countries is scarce. The purpose of this article is to two fold: first, to contribute to the already existing literature, and, secondly, and perhaps more importantly, to provide a foundation for prospective readers to better understand literature regarding educational services for students with mental retardation. This article guides the reader to understand the perspectives towards students with mental retardation, discusses the definition and causes of this condition, and discusses issues pertaining to the identification, assessment and evaluation of these students in Kenya. The core of the article contains a discussion of the various placement options available for this population along with the curriculum in operation in the various settings. Existing barriers to effectively serving this population in Kenya and in other developing countries is also discussed.
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Mapping the Word Reading Circuitry in Skilled and Disabled Readers - Pugh, K.R.; Frost, S.J.; Sandak, R.; Landi, N.; Moore, D.; Porta, G.D.; Rueckl, J.G.; Einar Mencl, W. (The Neural Basis of Read., 2010)
This chapter describes recent studies designed to generate data not only on the localization of reading-related brain activation, but also to examine patterns of interactions and dynamic trade-offs among these distributed reading-related systems. It begins with a review of relevant behavioral studies of component processing in fluent reading, with particular emphasis on the role of early (sublexical) phonology. It then discusses the current literature on the neurobiology of skilled and disabled reading, along with consideration of a series of recent studies that aim to capture brain correlates of component processing, again with an emphasis on phonological processing, adaptive learning, and complex trade-offs and interactions. Finally, it takes stock of what is considered to be crucial next steps (both technical and theoretical) in the emerging cognitive neuroscience of reading and its disorders. © Oxford University Press, 2014.
Journal Abbreviation: The Neural Basis of Read.
Keywords: Neurobiology; Reading disability; Reading systems; Skilled reading; dept.sed

Patterns of reading disabilities across development - Spear-Swerling, L. (Handbook of Reading Disability Research, 2010)
Journal Abbreviation: Handb. of Read. Disabil. Res.
Keywords: dept.sed

Assessment for research among deaf and hard of hearing students - Gabriel, R.; Dostal, H. (Ethical Issues in Literacy Research, 2013)
Journal Abbreviation: Ethical Issues in Lit. Research
Keywords: dept.sed

Hands-On Professional Development: Middle School teachers' Experiences with a Curriculum Intervention Research Project: This Study Explores the Benefits of a University-School Partnership That Impacted 26 Middle School Teachers in Four Urban Schools - Green, J.D.; Gonzalez, E.M.; López-Velásquez, A.M.; Howard, E.R. (Middle School Journal, 2013)
5 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Technology in Action - Newton, D.A.; Eren, R.; Ben-Avie, M. (Journal of Special Education Technology, 2013)
1 citations (Crossref) [2023-10-31]
Keywords: dept.sed

An information-processing framework for understanding reading disability - Spear, L.C.; Sternberg, R.J. (Handbook of Cognitive, Social, and Neuropsychological Aspects of Learning Disabilities, 2014)
Several years ago, when the senior author of this chapter taught in a resource room for learning-disabled children, she made a disturbing discovery. This discovery involved the reading-disabled youngsters, who comprised the majority of the children in the program. All these youngsters entered the program with poor decoding skills, but once exposed to the intensive phonic program used in the resource room, they generally learned to decode individual words with alacrity; that is, they could grasp phonic rules, memorize sounds for various letters and letter combinations, and apply the rules and sounds when reading individual words. The disturbing thing, particularly to someone who had had excessive faith in the curative powers of a phonic approach to teaching reading, was that the children continued to be poor readers. Now, however, their difficulties involved higher level aspects of reading. Their oral reading was discontinuous, effortful, and sometimes painfully slow; their reading comprehension was frequently poor; and the older children lacked the study strategies so important for success in content area subjects such as social studies and science. © 2014, Stephen J. Ceci. All rights reserved.
Journal Abbreviation: Handb. of Cognitive, Soc., and Neuropsychological Aspects of Learning Disabilities
Keywords: dept.sed

A professional development training model for improving co-teaching performance - Faraclas, K.L. (International Journal of Special Education, 2018)
Co-teaching is a promising practice for educating students with disabilities in regular education classes. However, teachers often report being given co-teaching assignments without requisite training. Without adequate preparation, many teachers have difficulty conceptualizing coteaching as a model and working collaboratively as teaching partners, often creating a division of labor that relegates special educators to a "helper" role in the classroom. This experimental study utilized a randomized pretest-posttest control group design to study the effects of a professional development training package on the collaborative teaching performance of regular and special education teachers. Analysis of covariance showed that teachers who participated in professional development training on co-teaching had significantly higher posttest scores on a co-teaching performance assessment than those who did not participate in training. © 2019, International Journal of Special Education. All rights reserved.
Keywords: Co-teaching; Collaboration; Effective teaching; Inclusion; Professional development; Research; Special education; Students with disabilities; Teacher education; Teacher training; dept.sed; peer-reviewed; ⛔ No DOI found

Book Review: Joseph Dorinson: Kvetching and Shpritzing: Jewish Humor in American Popular Culture : view - Saltman, J.M. (Humor, 2018)
0 citations (Crossref) [2023-10-31] ISBN: 09331719 (ISSN) Publication Title: Humor
Keywords: book.review; dept.sed

Can we get there from here? Learning disabilities and future edueation poliey - Spear-Swerling, L. (Perspectives on Learning Disabilities: Biological, Cognitive, Contextual, 2018)
Contemporary educational policies for identifying learning disabilities (LD) have been widely criticized. I would like to begin this chapter with a story that illustrates some of the conundrums in these policies. © 1999 Taylor & Francis.
Journal Abbreviation: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual
Keywords: dept.sed

Perspectives on learning disabilities: Biological, cognitive, contextual - Sternberg, R.J.; Spear-Swerling, L. (Taylor and Francis, 2018)
This book discusses biological, cognitive, educational, sociological, and interactive to discuss the nature of learning disabilities, its origins, its diagnosis, and effective remediation. It emphasizes the development of ideas as the motor forces behind the economic policies. © 1999 Taylor & Francis.
Journal Abbreviation: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual Pages: 296 Publication Title: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual
Keywords: dept.sed

Preface - Sternberg, R.J.; Spear-Swerling, L. (Perspectives on Learning Disabilities: Biological, Cognitive, Contextual, 2018)
Keywords: dept.sed; ⛔ No DOI found

What are we optimizing for in autism screening? Examination of algorithmic changes in the M-CHAT - Schjølberg, Synnve; Shic, Frederick; Volkmar, Fred R.; Nordahl-Hansen, Anders; Stenberg, Nina; Torske, Tonje; Larsen, Kenneth; Riley, Katherine; Sukhodolsky, Denis G.; Leckman, James F.; Chawarska, Katarzyna; Øien, Roald A. (Autism research : official journal of the International Society for Autism Research, 2021)
The present study objectives were to examine the performance of the new M-CHAT-R algorithm to the original M-CHAT algorithm. The main purpose was to examine if the algorithmic changes increase identification of children later diagnosed with ASD, and to examine if there is a trade-off when changing algorithms. We included 54,463 screened cases from the Norwegian Mother and Child Cohort Study. Children were screened using the 23 items of the M-CHAT at 18 months. Further, the performance of the M-CHAT-R algorithm was compared to the M-CHAT algorithm on the 23-items. In total, 337 individuals were later diagnosed with ASD. Using M-CHAT-R algorithm decreased the number of correctly identified ASD children by 12 compared to M-CHAT, with no children with ASD screening negative on the M-CHAT criteria subsequently screening positive utilizing the M-CHAT-R algorithm. A nonparametric McNemar's test determined a statistically significant difference in identifying ASD utilizing the M-CHAT-R algorithm. The present study examined the application of 20-item MCHAT-R scoring criterion to the 23-item MCHAT. We found that this resulted in decreased sensitivity and increased specificity for identifying children with ASD, which is a trade-off that needs further investigation in terms of cost-effectiveness. However, further research is needed to optimize screening for ASD in the early developmental period to increase identification of false negatives. © 2021 The Authors. Autism Research published by International Society for Autism Research and Wiley Periodicals LLC.
4 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34837355/
Keywords: Article; Autism Spectrum Disorder; Autistic Disorder; Checklist; Child; Cohort Studies; Female; Humans; Infant; M CHAT R algorithm; M CHAT algorithm; Mass Screening; McNemar test; Mothers; algorithm; autism; checklist; child; cohort analysis; controlled study; cost effectiveness analysis; dept.sed; developmental stage; diagnostic accuracy; diagnostic test accuracy study; early diagnosis; false negative result; female; gold standard; human; infant; major clinical study; mass screening; mother; nonparametric test; peer-reviewed; procedures; process optimization; psychometry; reference value; scoring system; sensitivity and specificity; statistical significance

Partnering to create a core communication board to improve theater experiences - Tucker, Lauren (Assistive Technology Outcomes and Benefits, 2021)
This article outlines a partnership between a nonprofit theater in Connecticut and pre-service special education teachers at a local university. The goal of the collaboration was to increase the accessibility of the sensory-friendly performances and events designed for students in PK-12. The process of creating visual supports and a core communication board is shared, in addition to the designing of training and implementation phases. The project not only resulted in improved supports for the school-aged sensory-friendly events for the next season, but also in a demonstrable perspective shift on the importance of inclusivity and community communication supports among pre-service teachers and community members. © 2021, Assistive Technology Industry Association. All rights reserved.
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85114899160
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Initial support for a behavioral skills training package with computer-based instruction to teach conversation skills to adults with autism spectrum disorders, with an assessment of socially meaningful behavior change1 - Groskreutz, Nicole C.; Groskreutz, Mark P. (Evidence-Based Communication Assessment and Intervention, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: Article; Asperger syndrome; adolescent; adult; autism; behavior change; behavior therapy; clinical article; communication skill; computer aided design; conversation; dept.sed; follow up; human; parental attitude; patient attitude; peer-reviewed; skill; social validity

Transfer of writing skills across genres among deaf and hard of hearing elementary writers - Dostal, Hannah M.; Wolbers, Kimberly A.; Weir, Joan (International Journal of Educational Research, 2021)
Thirty-seven deaf and hard of hearing (DHH) students in grades four through six participated in a year of Strategic and Interactive Writing Instruction, an approach to writing instruction designed to be responsive to DHH students’ unique language experiences and profiles. The current study investigated the transfer of writing skills between genres by analyzing participants’ recount, information report, and persuasive writing samples at four time points: at the beginning of the academic year, immediately before genre-focused instruction, at the end of 9 weeks of instruction in a genre, and 9 weeks after the conclusion of instruction in a genre. Results from the study demonstrate that DHH students transfer genre-specific writing skills between genres. © 2021 The Authors
4 citations (Crossref) [2023-10-31]
Keywords: dept.sed; peer-reviewed

Preparing educators for inclusive bilingual education: A boundary crossing laboratory between professional groups - Martínez-Álvarez, P; López-Velásquez, A; Kajamaa, A (Cultural-Historical Psychology, 2021)
Teacher education programs prepare candidates for bilingual, English as a second language, or special education as separate professionals. This creates challenges when teaching bilingual children with disabilities. There is a need to cross boundaries combining expertise and preparing teachers for children's uniqueness. Responding to this need, the researchers organized a change laboratory with 14 professors and two State Department of Education consultants. The study explored boundary expressions and their relationship to the larger activity. It also looked at the learning that took place during boundary crossing efforts. Boundaries were identified around bilingual teacher preparation, cross-disciplinary programmatic, and paradigmatic aspects. While boundary crossing at the intrapersonal level and at the interpersonal level were important, the need to engage multiple institutions was centered. In addition, the discussion manifested that for inclusive bilingual education teacher preparation, there was a need to go beyond the institutional level to reach to policy makers and address the sociopolitical resistance against bilingual education. Throughout the study, participants engaged primarily in the epistemic learning actions of analyzing and modeling. Through volitional actions, the participants realized a renewed object for their activity. This study widens the understanding of possibilities for taking shared educational responsibility through boundary crossing between professionals in preparation programs. © 2021. All Rights Reserved.
1 citations (Crossref) [2023-10-31]
Keywords: dept.sed; peer-reviewed

The Diagnosis of Autism: From Kanner to DSM-III to DSM-5 and Beyond - Rosen, Nicole E.; Lord, Catherine; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2021)
In this paper we review the impact of DSM-III and its successors on the field of autism—both in terms of clinical work and research. We summarize the events leading up to the inclusion of autism as a “new” official diagnostic category in DSM-III, the subsequent revisions of the DSM, and the impact of the official recognition of autism on research. We discuss the uses of categorical vs. dimensional approaches and the continuing tensions around broad vs. narrow views of autism. We also note some areas of current controversy and directions for the future.
Keywords: Article; Asperger syndrome; Autism; Autism Spectrum Disorder; Autistic Disorder; Categorical; DSM; DSM-5; DSM-III; DSM-IV; Diagnostic and Statistical Manual of Mental Disorders; Dimensional; History; Humans; ICD-10; ICD-11; Psychology; Recognition; autism; clinical feature; clinical research; cognition; cultural factor; dept.sed; dept.swk; developing country; echolalia; ethnic group; human; language ability; medical history; peer-reviewed; pervasive developmental disorder not otherwise specified; psychiatric diagnosis; psychological aspect; race; sex difference; social class; symptom; tension

Literacy development at camp: Leveraging language models - Dostal, Hannah M.; Scott, Jessica A.; Weir, Joan; Kang, Ki Y.; Amadi-Ihebuzor, Chidinma; Bernard, Teri-Ann (Reading Teacher, 2021)
There is little research on effective educational experiences for deaf and hard-of-hearing (d/hh) children in Jamaica. Using a formative and design experiment framework, in this project we explored the potential efficacy of an intensive literacy camp that provided professional development for d/hh adults working in classrooms with d/hh children, and provided literacy instruction for elementary-age campers. We found that the children improved in all tested areas, and observations of d/hh adults provided evidence that with minimal training they were able to implement important facets of literacy instruction with the campers. Further research on these types of experiences and their potential for lasting impact after the camp is necessary. © 2021 International Literacy Association
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102715654
Keywords: dept.sed; peer-reviewed

Student perception on the impact of the Livescribe smartpen as an accommodation - Tucker, Lauren; Zamfir, Bogdan (Universal Access in the Information Society, 2021)
The goal of this exploratory qualitative study was to determine how students with disabilities in higher education are using the Livescribe smartpen in their note-taking process and the perceived impact on their academic tasks. Based on participant interviews, many are using the Livescribe smartpen for recording class lectures while taking notes and for engaging with the content outside of the class session. All but one participant reported a perceived positive impact from the use of the Livescribe pen. The positive impacts included improved focus, higher academic outcomes, independence, and capturing complete notes. One unexpected trend that was revealed is that the majority of the participants adjusted their use of the Livescribe smartpen accommodation based on the professor’s teaching style and course structure. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103414669
Keywords: Course structure; Higher education; Information science; Information systems; Note taking; Qualitative study; Software engineering; Student perceptions; Teaching styles; dept.sed; peer-reviewed

Seeing the forest and the trees: Disentangling autism phenotypes in the age of DSM-5 - Volkmar, Fred R.; Woodbury-Smith, Marc; Øien, Roald A. (Development and Psychopathology, 2021)
This paper, written in honor of Professor Ed Zigler, focuses on some of the themes in developmental disabilities research that were so central to his work. It has now been nearly 80 years since Leo Kanner first identified the prototypic form – early infantile autism – of what is now autism spectrum disorder. In this article we summarize the development of the concept and the important accumulation of knowledge over time that has now led us to the recognition of a broader autism phenotype just as, at the same time, the current official diagnostic system in the USA has narrowed the concept. We also address current controversies regarding autism as the diagnosis is impacted by age and developmental factors, gender, and cultural issues. In parallel to the work on intellectual deficiency and development pioneered by Zigler and his colleagues, we summarize some of the challenges for the years ahead.
8 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102496361
Keywords: Autism Spectrum Disorder; Autistic Disorder; Diagnostic and Statistical Manual of Mental Disorders; Humans; Phenotype; Psychology; Recognition; autism; dept.sed; human; peer-reviewed; phenotype

P. Thomas: I See Things Differently: A First Look at Autism - Kuvish (Journal of Autism and Developmental Disorders, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Motivating students with learning disabilities to read - Wei, Yan; Spear-Swerling, Louise; Mercurio, Mia (Intervention in School and Clinic, 2021)
Students may lack the motivation to read for many reasons, including inadequate access to interesting texts, limited encouragement to read for pleasure from adults, instructional practices that do not foster engagement in learning, or a history of reading failure. This article focuses on students with reading disabilities who may have a long-standing dislike of reading born of repeated negative experiences with learning to read. Motivating these students to read for pleasure may seem like an unattainable goal. However, past difficulties in reading do not necessarily mean that children will dislike reading forever. In conjunction with appropriate academic interventions, student interest in reading might be improved by motivational interventions aligned with a theoretical framework discussed in this article: (a) choosing interesting texts to read, (b) stimulating knowledge-based interest, and (c) enhancing task-based interest.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086673210
Keywords: dept.sed; peer-reviewed

The print exposure of teacher candidates in relation to their achievement and self-ratings of early reading experiences - Spear-Swerling, Louise; Wei, Yan; Dostal, Hannah; Hernandez, Brittney (Reading and Writing, 2020)
This study examined the print exposure of teacher candidates (N = 195) in relation to their GPAs, achievement in reading and writing on the SAT, and their self-ratings of their own early (K to Grade 5) reading experiences. Participants came from undergraduate and Masters programs in varied certification areas and from two different universities. Print exposure measures included author recognition tests for both fiction and nonfiction; a questionnaire about participants’ current voluntary reading habits for books, magazines, newspapers, and digital print media; and favorite authors/books questions. Exploratory factor analysis suggested four factors underlying the different print exposure measures: (1) fiction book reading volume; (2) current magazine and newspaper reading; (3) nonfiction book reading volume and (4) current book reading habits for enjoyment. Only fiction and nonfiction book reading volume related positively to participants’ achievement, in writing as well as reading, and to their early reading experience ratings. A subgroup of participants who had taken a specific reading methods course involving structured language content, and who had positive early reading experience self-ratings, had higher performance in the course than did participants with mixed or negative self-ratings, although the two groups did not differ in overall GPA. Findings support the view that different measures of print exposure tap somewhat different aspects of print exposure, with differing relationships to varied indicators of achievement. Results also support concerns about the reading volume and print exposure of some teacher candidates. © 2020, Springer Nature B.V.
2 citations (Crossref) [2023-10-31] WOS:000563131900009
Keywords: Print exposure; Reading; Reading habits; Teacher candidates; Teacher preparation; Writing; dept.sed; peer-reviewed

Transdisciplinary Approach Practicum for Speech-Language Pathology and Special Education Graduate Students - Weiss, Deborah; Cook, Barbara; Eren, Ruth (Journal of Autism and Developmental Disorders, 2020)
Speech-language pathology and special education graduate student teams participated in an intensive summer practicum for social communication skills with children with autism spectrum disorders, utilizing a transdisciplinary approach that aligned to the frameworks utilized for implementation science. Questionnaires measuring transdisciplinary approach knowledge and comfort level were administered pre/post-practicum. Results of the questionnaires, written daily team reflections, course evaluations, and a focus group interview indicated an increase in all measures, including an increased knowledge of TA, increased understanding and comfort level with the other discipline, and a higher level of confidence and openness in working collaboratively utilizing a transdisciplinary approach. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
12 citations (Crossref) [2023-10-31] WOS:000516272800002
Keywords: Academic Performance; Article; Autism Spectrum Disorder; Autism spectrum disorder; Child; Collaborative teaming; Communication; Education; Special; Female; Humans; Implementation science; Interdisciplinary Research; Interprofessional collaboration; Male; Special education; Speech-Language Pathology; Speech-language pathology; Students; Health Occupations; Surveys and Questionnaires; Transdisciplinary; academic achievement; autism; child; comfort; communication skill; course evaluation; dept.cmd; dept.sed; education; female; graduate student; health student; human; implementation science; interdisciplinary education; interdisciplinary research; interpersonal communication; interview; knowledge; male; peer-reviewed; pretest posttest design; priority journal; procedures; professional development; psychology; quantitative analysis; questionnaire; social competence; special education; speech disorder; teacher; training

Teachers’ literacy-related knowledge and self-perceptions in relation to preparation and experience - Spear-Swerling, Louise; Brucker, Pamela Owen; Alfano, Michael P (Annals of Dyslexia, 2005)
After rating their own literacy-related knowledge in three areas (knowledge about reading/reading development, phonemic awareness/phonics, and morpheme awareness/structural analysis), graduate teacher-education students completed five tasks intended to measure their actual disciplinary knowledge in these areas. Teachers with high levels of prior background (i.e., course preparation and experience) rated themselves as significantly more knowledgeable than did low-background teachers in all areas; high-background participants also significantly outperformed low-background participants on all tasks. However, even high-background teachers scored well below ceiling on the tasks. Regression analyses indicated that teachers' self-perceptions and knowledge were positively influenced by both level of preparation and teaching experience, although the influences on teachers' knowledge differed by task. Teachers had some accurate perceptions of their own knowledge, especially in the area of phonics. Results suggest that differentiating levels of preparation may be useful in studying teacher knowledge, and also support the notion of a substantial gap between research on reading and teacher preparation in reading.
57 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-385-164-145-266 tex.type: [object Object]
Keywords: *Faculty; *Phonetics; *Professional Competence; *Reading; *Self Concept; Adult; Certification; Child; Credentialing; Education; Graduate; Education; Special; Educational Measurement; Faculty; Female; Humans; Literacy; Male; Phonetics; Professional Competence; Professional development; Reading; Self Concept; Semantics; Teacher education; Teacher knowledge; Teacher perceptions; Teacher preparation; United States; Vocabulary; academic achievement; accreditation; adult; article; certification; child; dept.sed; education; female; human; linguistics; male; phonetics; professional competence; reading; self concept; semantics; university

Fourth graders' performance on a state-mandated assessment involving two different measures of reading comprehension - Spear-Swerling, Louise (Reading Psychology, 2004)
This study examined fourth graders' performance on two reading comprehension measures, involving a question-answering format and a cloze format, which were part of a state-mandated assessment. Word-level reading skills and oral language comprehension were important to success on both formats, but word accuracy had a stronger relationship to the cloze than to the question-answering measure. Language comprehension related strongly to both formats. The cognitive profiles associated with poor reading comprehension varied, but most often involved a specific difficulty in accuracy of pseudoword decoding. The results suggest that test format should be considered in interpreting reading comprehension performance and underscore the need to assess specific component abilities in reading.
31 citations (Crossref) [2023-10-31] Citation Key Alias: pop00053 tex.type: [object Object]
Keywords: dept.sed

Preparing novice teachers to develop basic reading and spelling skills in children. - Spear-Swerling, Louise; Brucker, Pamela Owen (Annals of Dyslexia, 2004)
This study examined the word-structure knowledge of novice teachers and the progress of children tutored by a subgroup of the teachers. Teachers' word-structure knowledge was assessed using three tasks: graphophonemic segmentation, classification of pseudowords by syllable type, and classification of real words as phonetically regular or irregular. Tutored children were assessed on several measures of basic reading and spelling skills. Novice teachers who received word-structure instruction outperformed a comparison group of teachers in word-structure knowledge at post-test. Tutored children improved significantly from pre-test to post-test on all assessments. Teachers' post-test knowledge on the graphophonemic segmentation and irregular words tasks correlated significantly with tutored children's progress in decoding phonetically regular words; error analyses indicated links between teachers' patterns of word-structure knowledge and children's patterns of decoding progress. The study suggests that word-structure knowledge is important to effective teaching of word decoding and underscores the need to include this information in teacher preparation.
92 citations (Crossref) [2023-10-31] Place: United States Spear-Swerling, Louise. Southern Connecticut State University, Department of Special Education and Reading, 501 Crescent Street, New Haven, CT 06515, USA. spearswerl11@southernct.edu
Keywords: *Dyslexia/th [Therapy]; *Education/td [Trends]; *Reading; Adult; Articulation Disorders; Articulation Disorders/rh [Rehabilitation]; Child; Dyslexia; Education; Faculty; Female; Health Knowledge; Attitudes; Practice; Humans; Male; Reading; adult; article; attitude to health; child; dept.sed; dyslexia; education; evaluation; female; human; male; reading; speech disorder; university

Teachers’ acquisition of knowledge about English word structure - Spear-Swerling, Louise; Brucker, Pamela Owen (Annals of Dyslexia, 2003)
Previous research suggests that teachers' knowledge about English word structure (e.g., the phonological structure of words and common orthographic patterns in English) may be limited, although this knowledge is important for effective teaching of word decoding. This study examined teacher education students' knowledge about word structure, and improvements in their knowledge as a result of instruction, using three tasks: graphophonemic segmentation, classification of pseudowords by syllable type, and classification of real words as phonetically regular or irregular. Participants came from a special education certification program and included both preservice and inservice teachers. Results indicated that prior preparation to teach reading influenced participants' initial performance on two of the three word-structure tasks (all but graphophonemic segmentation); however, prior experience in teaching reading did not influence word-structure knowledge. A subset of participants who received specific instruction about word structure improved their knowledge relative to a comparison group of teacher education students who did not receive word-structure instruction. Prior preparation did not influence participants' responsiveness to instruction. Conclusions support the viewpoint that teacher education must include information about English word structure for educators who will teach reading and suggest that sufficiently intensive instruction may be important in developing word-structure knowledge.
72 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/133-442-343-497-778 tex.type: [object Object]
Keywords: dept.sed

A literacy tutoring experience for prospective special educators and struggling second graders. - Spear-Swerling, Louise (Journal of Learning Disabilities, 2009)
This study examined the learning of teacher candidates taking a language arts course in a special-educator preparation program and that of the second graders they tutored in a supervised field component of the course. Teacher candidates' knowledge of literacy instruction was assessed using five knowledge tasks; children were assessed on several measures of basic reading and spelling skills as well as on their knowledge of phonics concepts such as syllable types. Teacher candidates generally had inaccurate perceptions of their knowledge at pretest, but their knowledge improved significantly on all tasks after course instruction. Tutored children improved significantly from pre- to posttest on all assessments. The study suggests that carefully designed literacy coursework with field experiences can benefit both prospective special educators and struggling readers.
38 citations (Crossref) [2023-10-31] Place: United States Spear-Swerling, Louise. Southern Connecticut State University, Department of Special Education & Reading, Haven, CT 06515, USA. SPEARSWERLL1@southernct.edu
Keywords: *Education; Professional/st [Standards]; *Education; Special/st [Standards]; *Educational Status; *Professional Competence/st [Standards]; *Reading; *Remedial Teaching/st [Standards]; Adolescent; Adult; Child; Culture; Curriculum; Curriculum/st [Standards]; Education; Professional; Education; Special; Educational Status; Female; Humans; Linguistics; Linguistics/ed [Education]; Male; Middle Aged; Phonetics; Professional Competence; Questionnaires; Reading; Remedial Teaching; Self Concept; Special education; Surveys and Questionnaires; Teacher education; Teacher knowledge; Teacher perceptions; Young Adult; adolescent; adult; article; child; cultural anthropology; curriculum; dept.sed; education; educational status; female; human; linguistics; male; middle aged; phonetics; professional competence; questionnaire; reading; self concept; standard; teaching; vocational education

Comparing teachers' literacy-related knowledge to their state's standards for reading - McCombes-Tolis, Jule; Feinn, Richard (Reading Psychology, 2008)
This study compared elementary and special education teachers' knowledge of when K-3 students develop key reading competencies, their knowledge of who is responsible for teaching K-3 students key reading competencies, and teachers' perceptions of their own instructionally relevant competencies to those standards articulated within their state's blueprint for reading achievement. Results reveal a disconnect between teacher-held beliefs and state-articulated grade-level student literacy competencies. Results also suggest that teacher preparation programs are not preparing candidates to achieve mastery of essential teacher competencies articulated within their state's reading blueprint. Strengthening the accountability of teacher preparation practices to states' reading blueprint standards is recommended. Copyright © Taylor & Francis Group, LLC.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-545-510-020-506 tex.type: [object Object]
Keywords: dept.sed

School-wide intervention in the childhood bullying triangle - Mcnamee, Abigail; Mercurio, Mia (Childhood education, 2008)
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-117-892-896-643 tex.type: [object Object]
Keywords: dept.sed

Effective Social Interaction Strategies for Inclusive Settings. - Terpstra, Judith; Tamura, Ronald (Early Childhood Education Journal, 2008)
Many strategies and interventions exist in the education of young children with disabilities. One area of intervention is that of social interaction, including social skills instruction, peer interaction strategies, and play skills. Interaction and social skill strategies for use with children with and without disabilities for the purpose of increasing social interactions between children with and without disabilities in educational settings is an area many educators of early childhood special education strive to find in an effective and easy to implement format. Several strategies from research are presented in this article. Only strategies that were demonstrated to be successful through reported research are discussed. Strategies are identified according to their ease of implementation and effectiveness., (C)2008 Kluwer Academic Publishers
26 citations (Crossref) [2023-10-31] Place: (C)2008 Kluwer Academic Publishers
Keywords: Peer interaction; Play skills; Play strategies; Social interaction; Social skills; Social strategies; dept.sed

Children's reading comprehension and oral reading fluency in easy text - Spear-Swerling, Louise (Reading and Writing, 2006)
This study explored third-graders' oral reading fluency (ORF) in easy text in relation to their third- and fourth-grade reading comprehension. It also examined the children's performance on two different measures of text exposure, a self-report questionnaire and a title-recognition test. Although third-graders' ORF related significantly to their reading comprehension, oral language comprehension accounted for most of the variance in reading comprehension, whereas single word reading speed accounted for most of the variance in ORE Third-grade reading comprehension and ORF each predicted unique variance in children's scores on a fourth-grade state-mandated reading comprehension assessment. Scores on the self-report questionnaire correlated significantly with third-grade ORF and fourth-grade reading; the self-report accounted for reliable variance in ORF even with all of the other reading ability variables entered first. Results are consistent with the viewpoint that text exposure affects reading fluency. They also demonstrate that ORF is a valuable predictor of middle-elementary children's reading comprehension, even when the ORF measure employs very easy text in which children achieve near-perfect word accuracy.
40 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/050-531-179-017-917 tex.type: [object Object]
Keywords: Comprehension; Fluency; Reading; Text exposure; dept.sed; peer-reviewed

Core dimensions of autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L.J. (New Oxford Textbook of Psychiatry, 2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that manifests during the early developmental period of childhood. Behaviourally characterized by impairments in social interaction and communication, in combination with stereotyped and restricted patterns of behaviour and/or interest, it is currently believed that ASD occurs in approximately 1–2% of individuals. ASD is more prevalent among males than females (4–5:1), but the mechanisms resulting in this discrepancy are still unclear. This chapter will serve as an introduction to ASD, covering the topics of disorder history, prevalence rates, demographics, diagnostic criteria, differential diagnosis, and discussions on current and future diagnostic classification systems. The remaining chapters within Section 4 will then provide detailed discussions on more specific topics related to ASD, including current understandings of treatment planning, prevention and epidemiology, genetics, imaging, and disorder management.
tex.ids: volkmarCoreDimensionsAutism2020a
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2010)
1 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2010)
2 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2011)
3 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2011)
22 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G.; Walker, Harry (Journal of Special Education Technology, 2011)
22 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Deaf writers' application of american sign language knowledge to english - Wolbers, Kimberly A; Bowers, Lisa M; Dostal, Hannah M; Graham, Shannon C (International Journal of Bilingual Education and Bilingualism, 2014)
Language transfer theory elucidates how first language (L1) knowledge and grammatical features are applied in second language (L2) writing. Deaf and hard of hearing (d/hh) students who use or are developing American Sign Language (ASL) as their L1 may demonstrate the use of ASL linguistic features in their writing of English. In this study, we investigated the extent to which 29 d/hh students in Grades 6-8 (mean age=13.2) with diverse ASL exposure incorporated ASL features in their English writing. We also investigated the impact of one year of Strategic and Interactive Writing Instruction (SIWI) to increase students' metalinguistic knowledge and linguistic competence, and subsequently reduce ASL features in writing. Results indicate that ASL transfer is found in the writings of students with varied L1 experiences, and that SIWI can lead to significant reductions of ASL features in writing. The findings suggest that bilingual literacy programs where there is an emphasis on implicit language competence and metalinguistic knowledge can support d/hh students in the development of written English.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/092-626-258-729-096 tex.type: [object Object]
Keywords: ASL; bilingual education; deaf; dept.sed; language transfer; writing

Perspectives on Learning Disabilities: The Vectors of a New Convergence - Barsch, Ray H. (Journal of Learning Disabilities, 2016)
Learning disabilities is what this Journal is about. In the following article, Dr. Barsch sets forth past, present and possibilities for the future of the field...
5 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1968ZE76300001 tex.unique-id: [object Object]
Keywords: dept.sed

Reading achievement in the middle school years: A study investigating growth patterns by high incidence disability. - Yakimowski, Mary E.; Faggella-Luby, Michael; Kim, Yujin; Wei, Yan (Journal of Education for Students Placed at Risk, 2016)
Numerous research studies (e.g., Anderson, Kutash, & Duchnowski, 2001; Lane, Carter, Pierson, & Glaeser, 2006; Volpe, Dupaul, Jitendra, & Tresco, 2009; Wei, Blackorby, & Schiller, 2011) have shown that students with disabilities generally exhibit lower reading scores than their peers without disabilities. However, questions remain about the possibility of longitudinal differences among high-incidence disability classifications (e.g., speech/language impairments, SLI; emotional disturbances, ED; learning disabilities, LD; and attention deficit disorders, ADD). This study investigated growth patterns in reading achievement among middle school students from 5th to 8th grade with different high incidence disability classifications on one state's high-stakes assessment. After a repeated measures analysis of variance and post hoc testing, results reveal that students identified as LD and SLI evidenced more growth in reading than those classified as either ADD or ED. In light of the No Child Left Behind Act of 2001 legislation, findings about the various growth patterns are discussed with respect to policy, measurement, and practical implications. © 2016 Taylor & Francis Group, LLC.
12 citations (Crossref) [2023-10-31] Citation Key Alias: pop00217 tex.type: [object Object]
Keywords: dept.sed

Prosody growth and reading comprehension : a longitudinal study from 2nd through the end of 3rd grade - Lopes, João; Silva, Maria Madalena; Moniz, Antonio Vargas; Spear-Swerling, Louise; Zibulsky, Jamie (Revista De Psicodidactica, 2014)
Prosody is an important but not fully understood component of reading. In this longitudinal study with a sample of 98. Portuguese elementary school children, a multilevel growth model with four repeated measures over time showed steady progress in participants’ reading prosody from the middle of 2nd to the end of 3rd grade. However, children’s growth in this area varied across time points. Results also showed that individual differences in prosody’s scores at baseline affect the performance of most but not of all students. Simple linear regressions showed that the prosody dimension “phrasing/expression” significantly predicted reading comprehension at all time points. Partial correlation analysis showed that when reading rate was accounted for, the unique contribution of prosody to reading comprehension was marginal, except at the third measurement © UPV/EHU.
10 citations (Crossref) [2023-10-31] Citation Key Alias: pop00144 tex.type: [object Object]
Keywords: Prosody; Reading comprehension; Reading prosody; dept.sed

Making time for literacy: teacher knowledge and time allocation in instructional planning - Spear-Swerling, Louise; Zibulsky, Jamie (Reading and Writing, 2014)
This study examined how K-5 general and special educators (N = 102) would choose to allocate time in a 2-h language arts block if they could do so as they wished, and how these choices related to their knowledge base for reading instruction. Preferences for time allocation were assessed through an open grid on which participants listed descriptions of planned instructional activities and amount of time for each activity; teacher knowledge was assessed via a multiple-choice measure involving questions about assessment and instruction in the five components of reading. Results showed that many teachers planned little or no time for areas such as assessment, vocabulary, phonemic awareness, and spelling; also, relatively little time was devoted to basic writing skills and virtually none to writing processes such as planning or revision. There were few significant differences between general and special educators in time allocation on the grid, although there were more differences by grade level (e.g., grids for Grades K-1 vs. Grades 4-5). Teacher knowledge did predict teachers' time allocation plans, particularly for teachers with relatively high knowledge of phonemic awareness and phonics. Overall, however, many teachers chose to allocate time in ways inconsistent with scientific recommendations, in writing as well as in reading. The study highlights the importance of research-based, targeted teacher professional development in literacy, as well as the need for schools to provide comprehensive, research-based core reading and writing curricula to educators, with attention to fidelity of implementation.
40 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-473-976-832-915 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Literacy; Reading; Reading instruction; Teacher beliefs; Teacher knowledge; Writing instruction; dept.sed; peer-reviewed

Teachers' knowledge base for implementing response-to-intervention models in reading - Spear-Swerling, Louise; Cheesman, Elaine (Reading and Writing, 2012)
This study examined the knowledge base of 142 elementary-level educators for implementing response-to-intervention (RTI) models in reading. A questionnaire assessed participants' professional background for teaching reading, as well as their familiarity with specific assessments, research-based instructional models, and interventions potentially useful in RTI approaches. A multiple-choice knowledge survey patterned after a teacher licensure exam, including items situated in classroom contexts, assessed participants' knowledge about different components of reading, assessment, and RTI practices. Overall, participants obtained the highest scores on a knowledge survey subscale involving fluency/vocabulary/comprehension and the lowest on a subscale involving assessment/RTI practices, with a subscale involving phonemic awareness/phonics in the middle. Mean percentages correct on the subscales ranged from about 58-65% correct. However, participants who said they had prior code-focused professional development outperformed other participants on all survey subscales. General elementary certified teachers performed comparably to special education certified teachers on two out of three subscales, with both groups outperforming unlicensed participants; on the assessment/RTI subscale, only the special educators outperformed unlicensed participants. Most participants were familiar with basic features of RTI such as the three tiered model but were unfamiliar with the research-based instructional approaches and interventions named in the study questionnaire, although participants who had experienced code-focused PD were significantly more likely to be familiar with certain interventions. The study suggests that professional development will be important to enable many educators to implement RTI effectively in reading.
53 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/067-538-663-824-787 tex.unique-id: [object Object]
Keywords: Literacy; RTI; Reading; Response to intervention; Teacher knowledge; Teacher preparation; dept.sed; peer-reviewed

Effects of varied levels of treatment integrity on appropriate toy manipulation in children with autism - Groskreutz, Nicole C.; Groskreutz, Mark P.; Higbee, Thomas S. (Research in Autism Spectrum Disorders, 2011)
We assessed the effects of varying the treatment integrity of a prompting procedure on appropriate toy manipulation in two preschool-aged children with autism. Following an assessment to identify toys with high levels of inappropriate toy manipulation, each of three toys was associated with implementation of the prompting procedure at a different integrity level (10%, 50%, or 100%). For one participant, only the 100% integrity condition produced increases in appropriate toy manipulation. For the second participant, both the 50% and 100% integrity conditions produced increases in appropriate toy manipulation. These results suggest that integrity errors negatively impacted the acquisition of appropriate toy manipulation in children with autism, although the necessary level of treatment integrity varied across participants. (C) 2011 Elsevier Ltd. All rights reserved.
15 citations (Crossref) [2023-10-31] tex.researcherid-numbers: Higbee, Thomas S/F-5157-2010 tex.unique-id: ISI:000292235600009
Keywords: Autism; Play skills; Toy manipulation; Treatment integrity; article; autism; case report; child; dept.sed; human; learning; machiavellianism; male; play therapy; preschool child; priority journal; psychologic assessment; treatment planning

Practicing Evidence-Based Practices - Eren, Ruth Blennerhassett; Brucker, Pamela Owen (Evidence-Based Practices and Treatments for Children with Autism, 2011)
Public education in the United States has a history of local control in the development of curriculum and instruction. Although notable court decisions have led to more universal applications of educational policy and practices (Brown v. Board of Education 1954, Oberti v. Clementon 1993), it has been federal law that has resulted in significant changes in instruction. The Individuals with Disabilities Education Improvement Act (IDEA; Public Law 108–142), first enacted in Public Law 94–142, guaranteed the right of a free, appropriate public education for all children, regardless of the severity of their disability. The word “appropriate” resulted in the beginning of what we refer to today as differentiated instruction: instructional strategies that allow a child to learn and progress in an educational setting. The federal law, No Child Left Behind (NCLB; Public Law 107-110), enacted in 2001, contributed to this initiative and added a caveat that these differentiated instructional strategies needed to be grounded in scientifically based research. Indeed, the term “scientifically based research” has been noted to appear in NCLB 111 times (Deshler 2002). The federal government, in IDEA 2004, identified 13 eligibility categories. In order to receive special education services, a student must, through a multidisciplinary evaluation, meet the eligibility criteria established for one of the 13 categories. Since 1975, when PL94–142 was enacted, educational interventions for students receiving special education have expanded, particularly in disability categories with a high level of incidence such as speech and language disorders and learning disabilities. Low-incidence disabilities, such as mental retardation, visual impairments, and autism, have received less attention.
Citation Key Alias: lens.org/104-519-704-094-108
Keywords: General Education; Individualize Education Program; Special Education; Special Education Teacher; Team Meeting; dept.sed

Relationships between sixth-graders' reading comprehension and two different measures of print exposure. - Spear-Swerling, Louise; Brucker, Pamela; Alfano, Michael (Reading and Writing, 2010)
This study examined sixth-graders' reading comprehension and component reading abilities in relation to two measures of print exposure: an author recognition test (ART) involving fiction authors and a reading habits questionnaire (RHQ) about children's voluntary reading for enjoyment across various genres. The ART correlated only with children's fiction book reading habits, not with other habits such as nonfiction book or magazine reading, and had a stronger relationship to all tested reading abilities than did the RHQ. Strong comprehenders in reading outperformed weak comprehenders on all component reading measures, ART score, and fiction habits; however, weak comprehenders scored higher than did strong comprehenders on the indicator of nonfiction reading habits. The two groups of comprehenders did not differ significantly on other reported reading habits. The results are discussed in relation to children's specific book choices and demonstrate the relevance of genre to evaluations of children's print exposure., (C)2010 Kluwer Academic Publishers
41 citations (Crossref) [2023-10-31] Place: (C)2010 Kluwer Academic Publishers
Keywords: Author recognition tests; Print exposure; Reading; Reading comprehension; Reading habits; dept.sed; peer-reviewed

Common types of reading problems and how to help children who have them - Spear-Swerling, Louise (Reading Teacher, 2016)
Patterns of reading difficulty provide an educationally useful way to think about different kinds of reading problems, whether those problems are mainly experiential in nature (e.g., those common among English learners) or associated with disabilities (e.g., those typical of children with dyslexia). This article reviews research on three common patterns of poor reading: specific word-reading difficulties, specific reading-comprehension difficulties, and mixed reading difficulties. The purpose of the article is to explain how teachers can use assessments to identify individual struggling readers' patterns of reading difficulties, and how this information is valuable in differentiating classroom instruction and planning interventions.
13 citations (Crossref) [2023-10-31] tex.eissn: 1936-2714 tex.unique-id: ISI:000372317700007
Keywords: Diagnostic; Instructional intervention; Instructional strategies; dept.rdg; dept.sed; peer-reviewed; teaching strategies

How Portuguese and American teachers plan for literacy instruction. - Spear-Swerling, Louise; Lopes, Joao; Oliveira, Celia; Zibulsky, Jamie (Annals of Dyslexia, 2016)
This study explored American and Portuguese elementary teachers' preferences in planning for literacy instruction using the Language Arts Activity Grid (LAAG; Cunningham, Zibulsky, Stanovich, & Stanovich, 2009), on which teachers described their preferred instructional activities for a hypothetical 2-h language arts block. Portuguese teachers (N = 186) completed Portuguese versions of a background questionnaire and LAAG electronically, in Survey Monkey; American teachers (N = 102) completed identical English measures using paper and pencil. Results showed that teachers in both groups usually addressed comprehension and reading fluency on their LAAGs and that they also allocated the most time to these two areas. However, American teachers were more likely to include teacher-directed fluency activities, whereas Portuguese teachers were more likely to include fluency activities that were not teacher directed. Significantly more American than Portuguese teachers addressed phonics in their planning, whereas significantly more Portuguese than American teachers addressed writing processes such as revision. Both groups of educators demonstrated large variability in planning, with many teachers omitting important components of literacy identified by researchers, for writing as well as reading. The study highlights the importance of providing teachers with comprehensive, research-based core literacy curricula as well as professional development on key components of literacy. Study findings also suggest significant relationships between orthographic transparency and teachers' instructional planning.
5 citations (Crossref) [2023-10-31] Place: United States Spear-Swerling, Louise. Department of Special Education and Reading, Southern Connecticut State University, 501 Crescent St., New Haven, CT, 06515, USA. SPEARSWERLL1@southernct.edu. Lopes, Joao. School of Psychology, Department of Applied Psychology, University of Minho, Campus de Gualtar, 4710-057, Braga, Portugal. Oliveira, Celia. Lusofona University of Porto, Rua Augusto Rosa, no 24, 4000-098, Porto, Portugal. Zibulsky, Jamie. Psychology Department, T-WH1-01, Fairleigh Dickinson University, 1000 River Road, Teaneck, NJ, 07666, USA.
Keywords: *Language Arts; *Literacy; *School Teachers; *Teacher Training; Adult; Comprehension; Cross-linguistic; Curriculum; Female; Humans; Language Arts; Literacy; Male; Phonetics; Portugal; Reading; School Teachers; Teacher Training; Teacher beliefs; Teacher education; Teacher knowledge; United States; Writing; Young Adult; adult; comprehension; curriculum; dept.rdg; dept.sed; female; human; language; literacy; male; phonetics; school teacher; teacher training; young adult

Valuing stuff materials culture and artifactual literacies in the classroom - Randall, Regine; Mercurio, Mia Lynn (Journal of Adolescent & Adult Literacy, 2015)
Recent interest in materials culture and artifactual literacies has helped the authors of this article rethink how they teach preservice and inservice teachers and collaborate with K-12 teachers. Each discipline has its own stuff that can help students understand the products and practices of a field beyond what they might be able to glean from text. To that end, every teacher should see their classroom and content area as a "place for my stuff" because objects speak and communicate more messages through form, color, size, and texture than print alone. © 2015 International Literacy Association.
1 citations (Crossref) [2023-10-31] tex.eissn: 1936-2706 tex.unique-id: ISI:000363658800011 Citation Key Alias: ISI:000363658800007
Keywords: 3-Early adolescence; 4-Adolescence; 5-College/university students; Adolescent/young adult literature; Content analyses; Content literacy; Discussion strategies; Information literacy; Informational text; Instructional strategies; Literary elements; Specific subject areas (math; Strategies; Text types; and materials; art; dept.cur; dept.sed; etc.); methods; teaching strategies; text features

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks; manuals; etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection

College Access, Success and Equity for Students on the Autism Spectrum. - Accardo, Amy L; Bean, Kimberly; Cook, Barbara; Gillies, Ann; Edgington, Rebecca; Kuder, S Jay; Bomgardner, Estyr M (Journal of autism and developmental disorders, 2019)
College may be considered a gateway to success, yet access to college is limited for young adults with autism. Given the research recommendations to elicit student experiences and to communicate among universities to improve college access, success, and equity, the present study examined the questions: What factors are perceived as pathways to success or barriers to success by college students on the autism spectrum? What university provided accommodations and/or support services do they prefer? Participants from four universities completed surveys and semi-structured interviews. Findings from the multi-university study suggest the need to provide transition planning and systematic non-academic social and emotional supports from the start of the college experience as well as specific training for faculty, staff, and peers.
20 citations (Crossref) [2023-10-31] Place: United States Accardo, Amy L. College of Education, Rowan University, 201 Mullica Hill Road, Glassboro, NJ, 08028, USA. Accardo@rowan.edu. Bean, Kimberly. School of Education, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Cook, Barbara. School of Health and Human Services, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Gillies, Ann. Colorado Mesa University, 1100 North Ave, Grand Junction, CO, 81501, USA. Edgington, Rebecca. Eastern Illinois University, 600 Lincoln Ave, Charleston, IL, 61920, USA. Kuder, S Jay. College of Education, Rowan University, 201 Mullica Hill Road, Glassboro, NJ, 08028, USA. Bomgardner, Estyr M. College of Education, Rowan University, 201 Mullica Hill Road, Glassboro, NJ, 08028, USA.
Keywords: *Academic Success; *Autism Spectrum Disorder/rh [Rehabilitation]; *Mainstreaming; Education/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Academic Success; Accommodations; Adolescent; Article; Autism Spectrum Disorder; Autism Spectrum Disorder/px [Psychology]; Autism spectrum disorder; College; Female; Humans; Mainstreaming; Education; Male; Mental health; Students; Students/px [Psychology]; Students/sn [Statistics & Numerical Data]; Universities; University; Young Adult; academic success; adolescent; adult; autism; college; college student; dept.cmd; dept.sed; disability; executive function; female; financial management; follow up; health equity; human; longitudinal study; male; mental health care; motivation; peer-reviewed; priority journal; psychology; self concept; semi structured interview; social network; social support; student; student attitude; university; young adult

What's a middle school teacher to do? Five evidence-based practices to support English learners and students with learning disabilities - Hovey, Katrina A.; Miller, Rhonda D.; Kiru, Elisheba W.; Gerzel-Short, Lydia; Wei, Yan; Kelly, Jerae (Preventing School Failure: Alternative Education for Children and Youth, 2019)
General education teachers are challenged with meeting the unique instructional needs of every learner in their classrooms, which increasingly include English learners (ELs) and students with learning disabilities (LD). This article uses vignettes to demonstrate how a middle school content teacher uses five strategies: building prior knowledge, building vocabulary, explicit instruction, visual representation, and opportunities to respond to support his students. Each strategy is evidence based for ELs and for students who have an identified LD. Research supports that ELs and students with LD benefit from specific instructional strategies that enhance the accessibility of course content and potentially improve learning outcomes. © 2019, © 2019 Taylor & Francis Group, LLC.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-310-082-508-391, pop00124 tex.type: [object Object]
Keywords: English learners; dept.rdg; dept.sed; evidence-based strategies; instructional practices; learning disabilities; peer-reviewed

Teachers' academic training for literacy instruction - Oliveira, Celia; Lopes, Joao; Spear-Swerling, Louise (European Journal of Teacher Education, 2019)
Literacy instruction is a powerful determinant of children's academic and school outcomes. Teachers' training for literacy instruction is therefore critical for children's reading learning. The present study examined the contents of 130 courses related to literacy instruction from a representative national sample of primary teachers' undergraduate programs (N =81), to address the following issues: which courses, related to literacy instruction, are included in the curriculum of undergraduate training programs? Which is the weight of the courses in undergraduate programs? What are the contents of the courses? The results show that most critical features of literacy instruction are included in the course contents of most programs (e.g. phonics, theory of literature). Still, some other critical features are underrepresented (reading/writing comprehension skills) or apparently missing (assessment and intervention in reading/writing problems). Moreover, the time allocated to literacy instruction seems to be scarce. Still, wide differences across university programs and courses were found.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/108-826-738-594-43X tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Literacy instruction; dept.sed; peer-reviewed; reading and writing; specific content knowledge; undergraduate teachers' training; undergraduate teachers’ training

Engaging culturally and linguistically diverse families of children with disabilities - Gerzel-Short, Lydia; Kiru, Elisheba W.; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan; Miller, Rhonda D. (Intervention in School and Clinic, 2019)
Classrooms are increasingly more diverse, and student success can be enhanced through family engagement, especially for culturally and linguistically diverse (CLD) students with disabilities. Too often teachers are stymied by how to engage CLD families of children with disabilities. Common practices of parent involvement are ineffective and fail to appreciate families as members of the educational team. Family engagement seeks to establish and maintain authentic family-school partnerships based on mutual respect and shared agency for student academic and social success. This column provides specific family engagement strategies that teachers and schools can implement in an effort to provide reciprocal collaboration.
9 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000490317000008, lens.org/119-272-627-527-661 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: cultural and linguistic diversity; dept.rdg; dept.sed; disabilities; diverse families; family engagement; family-school collaboration; multicultural; peer-reviewed

The challenges of recruiting and retaining dual language teachers - Howard, Elizabeth; López-Velásquez, Angela M. (Dual language education: teaching and leading in two languages, 2019)
Across the United States, the popularity of dual language education (DLE) has grown considerably over the past several decades, but finding qualified bilingual teachers to staff these programs is an ongoing issue for administrators. Using the Guiding Principles for Dual Language Education as a framework, this chapter addresses this urgent issue by exploring dual language teacher recruitment and retention through the experiences and recommendations of teachers and administrators in Connecticut. Findings address participants’ perceptions of teacher recruitment and retention, staff selection, workplace climate, and staff evaluation. Cross-cutting themes include the value of shared responsibility and shared decision-making in addressing this complex issue, the need for creativity and flexibility to increase pathways to certification for dual language teachers, and the importance of positive working conditions.
Citation Key Alias: howardChallengesRecruitingRetaining2019a, lens.org/002-643-691-422-714
Keywords: Alternative routes to certification; Bilingual teachers; Dual language; School climate; School-university partnerships; Teacher certification; Teacher recruitment; Teacher retention; Teacher shortage; dept.sed

Coteaching in content area classrooms: Lessons and guiding questions for administrators - Sinclair, Anne C.; Bray, Laura E.; Wei, Yan; Clancy, Erin E.; Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J. (NASSP Bulletin, 2018)
Secondary school administrators increasingly include students with disabilities in general education classrooms with coteaching models. Theoretically, coteaching enables two educators to attend to the learning needs of students with disabilities while exposing them to grade-level content area instruction. However, our study on teachers’ perceptions of coteaching found that teachers often viewed their schools’ leadership decisions as adversely affecting their ability coteach effectively. The purpose of this article is to provide administrators with an overview of common coteaching models, summarize findings from our study on teachers’ perceptions of how their schools’ leadership influenced their coteaching practices, and provide a set of guiding questions to consider when seeking to support coteaching. © 2018 SAGE Publications.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-514-925-194-03X, pop00123 tex.type: [object Object]
Keywords: coteaching; dept.rdg; dept.sed; inclusion; instructional leadership; peer-reviewed; professional development

Brief article of gratitude to Paul McGhee - Saltman, Joyce (Humor-International Journal of Humor Research, 2018)
0 citations (Crossref) [2023-10-31] tex.eissn: 1613-3722 tex.unique-id: ISI:000431127000005
Keywords: dept.sed; peer-reviewed

A high school replication of targeted professional development for classroom management - Freeman, Jennifer; Kowitt, Jennifer; Simonsen, Brandi; Wei, Yan; Dooley, Kate; Gordon, Lola; Maddock, Eleanor (Remedial and Special Education, 2018)
In areas of emerging research, such as supporting teachers' classroom management, replication of research is critical to ensuring that recommendations for the field are based on sound science and appropriate for the contexts to which they are being applied. This article describes a replication of research on efficient professional development supports for teachers' classroom managements in a new context: high school classrooms. Data did not support a functional relation between teachers' use of specific praise and the targeted professional development and self-management in the high school setting. Results of this study highlight the critical importance of replication in education research. Based on our findings and our experience conducting this study, we suggest several possible adaptations may be necessary for successful replication at the high school level.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/158-228-318-057-658, pop00145 tex.type: [object Object]
Keywords: behavior; dept.rdg; dept.sed; inservice training; management; peer-reviewed; personnel preparation; research methodology; secondary; single-subject; staff development/inservice

Reading comprehension and co-teaching practices in middle school English language arts classrooms - Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J.; Mitchell, Marisa; Clancy, Erin; Davidson, Kimberly A.; Sinclair, Anne C.; Wei, Yan (Exceptional Children, 2018)
This study reports practices implemented in over 2,000 minutes by 16 middle school special education and general education co-teaching pairs in English language arts classes. We report the extent to which teachers integrated literacy activities that support reading comprehension, the co-teaching models used, and the frequency with which each teacher led instruction. We also report the types of grouping structures teachers used and the extent to which teachers interacted with students with disabilities. Finally, we report the types of text used. Observations revealed that more than half of time spent on literacy activities involved reading aloud or silently with no co-occurring literacy instruction that supports reading comprehension. Students with disabilities spent a majority of their time in whole-class instruction or working independently with little teacher interaction. Special education teachers spent most of their time supporting whole-class instruction led by the content-area teacher. Implications and directions for future research are provided.
37 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-264-196-907-683, pop00086 tex.type: [object Object]
Keywords: dept.rdg; dept.sed; peer-reviewed

Higher education and disability: A systematic review of assessment instruments designed for students, faculty, and staff - Lombardi, Allison; Gelbar, Nicholas; Dukes, III, Lyman L.; Kowitt, Jennifer; Wei, Yan; Madaus, Joseph; Lalor, Adam R.; Faggella-Luby, Michael (Journal of Diversity in Higher Education, 2018)
In this study, the literature in disability and higher education was examined, with a specific focus on assessment instruments. Published articles (n = 203) on development of new or refinement of existing instruments were reviewed for traits measured and psychometric rigor reported. Findings showed instruments are intended for professionals and students, and of the student instruments, broad categories are academic, nonacademic, and specific to a disability diagnosis. Not all instruments are limited to students with disabilities; many of the reviewed instruments can be utilized in higher-education settings on all students, faculty, and staff, regardless of disability. The implications of the findings undergird the urgency to prioritize disability as a facet of diversity within higher-education scholarship, and furthermore aid this prioritization by providing a catalogue of robust instruments to researchers and practitioners.
25 citations (Crossref) [2023-10-31] tex.eissn: 1938-8934 tex.unique-id: ISI:000426973700003
Keywords: Disability; assessment; campus climate; dept.rdg; dept.sed; peer-reviewed; program evaluation

Brief report: Self-reported academic, social, and mental health experiences of post-secondary students with autism spectrum disorder - Jackson, Scott L. J.; Hart, Logan; Brown, Jane Thierfeld; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
104 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Reading comprehension strategies in autism spectrum disorders - Bean, Kimberly (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.sed

The need for caregiver support for families of children with ASD - Bean, Kimberly; Meers, K (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.sed

The bilingual reading practices and performance of two Hispanic first graders - López-Velásquez, Angela M.; García, Georgia Earnest (Bilingual Research Journal, 2017)
This qualitative study used a sociocultural lens to examine how two bilingual Hispanic first-grade girls demonstrated bilingual reading practices (i.e., heteroglossia and translanguaging) as they discussed and read texts in Spanish and English. One girl predominantly received school reading instruction in Spanish, while the other received school reading instruction in English. They both participated in Spanish reading at home. The school reading instruction employed Spanish or English versions of Success for All, and emphasized word recognition strategies appropriate for the language of instruction along with meaning-making strategies. In April, the two girls scored mid- to end-of first grade on a curriculum-based reading assessment in the language of instruction. Neither of them received biliteracy instruction. Their reading levels in the instructional language and exposure to the other language appeared to be sufficient for them to develop and demonstrate heteroglossic practices. Bilingual dynamic reading assessments and home reading sessions with a bilingual researcher revealed that both girls utilized bilingual reading practices to discuss and comprehend texts in their non-instructional or alternate language. One of the girls also used bilingual reading practices to discuss texts in the instructional language. To read in the alternate language, they both employed word-recognition and meaning-making strategies, which had been emphasized in their school reading instruction. However, one girl’s attempt to use a decoding strategy she had learned in English (i.e., onset-rime) to decode unfamiliar Spanish words did not work effectively. Implications are delineated for the bilingual reading instruction and assessment of young bilingual children.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-192-087-803-633, pop00095 tex.type: [object Object]
Keywords: dept.sed

Leveraging information technology literacy to enhance college and career readiness for secondary students with disabilities - Lombardi, Allison; Izzo, Margo V.; Gelbar, Nicholas; Murray, Alexa; Buck, Andrew; Johnson, Victor; Hsiao, Jay; Wei, Yan; Kowitt, Jennifer (Journal of Vocational Rehabilitation, 2017)
BACKGROUND: In the 21st century, information technology (IT) literacy is crucial for all students, and may better prepare students with disabilities for transition to postsecondary employment or education. OBJECTIVE: In this study, the potential of IT literacy embedded into an online transition curriculum is explored in the context of secondary special education. The curriculum aligns with Common Core State Standards in English Language Arts that are relevant to reading comprehension, writing, as well as searching for and analyzing sources of information online. METHODS: A quasi-experimental pretest-posttest design was utilized in six high schools. RESULTS: Findings show that intervention group students improved in IT literacy; whereas, comparison group students did not make similar gains. CONCLUSION: Implications for embedding transition services into specific courses and curricula for secondary students with Individualized Education Programs (IEPs) are discussed. © 2017-IOS Press and the authors. All rights reserved.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-237-439-502-729, pop00111 tex.type: [object Object]
Keywords: Article; Transition; adolescent; attention deficit disorder; autism; career; career readiness; college; comprehension; controlled study; curriculum; dept.rdg; dept.sed; disability; education program; emotional disorder; employment; female; high school student; human; information technology; intellectual impairment; language disability; learning disorder; literacy; major clinical study; male; quasi experimental study; special education; technology; vocational education; writing

Transition issues and challenges for youth with autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L. J.; Hart, Logan (Pediatric Annals, 2017)
49 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Participation of students with intellectual and developmental disabilities in extracurricular activities: does inclusion end at 3:00? - Agran, Martin; Achola, Edwin; Nixon, Cynthia Allen; Wojcik, Andrew; Cain, Irma; Thoma, Colleen; Austin, Kira M.; Tamura, Ronald B. (Education and Training in Autism and Developmental Disabilities, 2017)
Although participation in extracurricular activities for students with intellectual and developmental disabilities has been advocated, a limited number of students appear to be involved in such activities. Further, there is little empirical research on how extracurricular activities are valued, supported, and encouraged. This study surveyed a sample of special educators across five states to learn about their opinions regarding extracurricular activities. As reported in other research, the findings confirm that few students participated in these activities; few parents requested these services for their children; and few teachers believed that planning them is their responsibility, despite the fact that they thought these activities were of value and provided several benefits. The implications of these findings are discussed.
tex.unique-id: ISI:000395226900001
Keywords: dept.sed

Teaching students to write: Arguing against the overuse of argument - Randall, Régine; Mercurio, Mia Lynn (Kappa Delta Pi Record, 2017)
This personal editorial written by two education professors considers the Common Core State Standards and argues against the overuse of argument in the teaching of writing. © Kappa Delta Pi.
0 citations (Crossref) [2023-10-31]
Keywords: Common core; Writing; dept.cur; dept.sed

Exploring English and Spanish rhyme awareness and beginning sound segmentation skills in prekindergarten Spanish-speaking English Learners - Raynolds, Laura B.; López-Velásquez, Angela; Olivo Valentín, Laura E. (Reading and Writing, 2017)
Twenty-five 4- and 5-year-old Spanish-speaking English Learners (ELs) were tested in order to compare their English and Spanish performance in two phonological awareness skills: Rhyme awareness (RA) and beginning sound segmentation (BSS). The children had received formal instruction of phonological awareness, with an emphasis on RA and BSS for 1 year and in English only, using the Opening the World of Learning curriculum (Schickedanz & Dickinson, 2005). The results showed that the children scored higher on the English BSS than on the English RA tests (p ¡ .001), even though RA is generally considered to be an earlier developing skill than BSS among English-monolingual children. No significant difference was found between the English BSS and Spanish BSS tests despite the fact that the children had received English-only instruction in these phonological awareness skills for 1 year. The results are discussed in terms of the possible impact of the similarities and differences between the Spanish and English linguistic structures on the learning and cross-linguistic transfer of phonological awareness skills in young Spanish-speaking ELs.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000398445600003, lens.org/009-289-778-807-372 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Beginning sound segmentation; English-only instruction; Phonological awareness; Prekindergarten; Rhyme awareness; Spanish-speaking English Learners; dept.cur; dept.sed; peer-reviewed